Changing trends in the management of choledochal cysts in children in an Egyptian institution. Issue 3 (July 2016) - Hassan, Hussam S.
Abstract : Introduction/purpose: Choledochal cyst excision and biliary reconstruction is the treatment of choice for choledochal cysts. Biliary reconstruction is carried out using several methods. The two most popular procedures are Roux-en-Y hepaticojejunostomy and hepaticoduodenostomy (HD). Both techniques have their merits and drawbacks. The aim of this study was to detect the change in trends in the management of cases of choledochal cysts during the period from 1993 to 2005 compared with the period between 2006 and 2015. Patients and methods: The files of patients admitted in our institute during the period from 2006 to 2015 for the treatment of choledochal cysts were reviewed. The data of patient' demographics, pathology, presentation, investigations, surgery, and outcome were statistically analyzed. Data were compared with a previous study conducted at this institute a decade earlier. Results: Files of 25 patients were retrieved. Patients' demographics, pathology, and presentation were not statistically different between the two decades. There was a recent change in trend in management; all cases were operated using HD, except for those cases that required very high hepatointestinal anastomosis. HD had a significantly shorter operative time. Operation outcome and long-term follow-up were comparable between the two decades. Conclusion: HD is the preferred option for biliary reconstruction in our institute. This was based on the shorter operative time and avoidance of intestinal anastomosis, and an early and late complication rate compared with Roux-en-Y hepaticojejunostomy.